2021
DOI: 10.1210/clinem/dgab415
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Insulin Sensitivity and Menstrual Cycle Is Modified by BMI, Fitness, and Physical Activity in NHANES

Abstract: Context There is evidence demonstrating variation in insulin sensitivity across the menstrual cycle. However, to date, research has yielded inconsistent results. Objective This study investigated variation in insulin sensitivity across the menstrual cycle and associations with BMI, physical activity and cardiorespiratory fitness. Design Data from 1906 premeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 39 publications
2
32
1
1
Order By: Relevance
“…Hence, the nutritional state could additionally modulate the brain’s response to food cues [ 35 , 42 , 51 , 55 57 ], though, the detailed underlying mechanisms remain unclear. Furthermore, hormonal fluctuations during the menstrual cycle have shown to influence peripheral and central insulin sensitivity [ 58 , 59 ]. Hence, further studies are needed to evaluate the complex interplay of sex hormones and nutritional state on the brain response to physiological and environmental cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the nutritional state could additionally modulate the brain’s response to food cues [ 35 , 42 , 51 , 55 57 ], though, the detailed underlying mechanisms remain unclear. Furthermore, hormonal fluctuations during the menstrual cycle have shown to influence peripheral and central insulin sensitivity [ 58 , 59 ]. Hence, further studies are needed to evaluate the complex interplay of sex hormones and nutritional state on the brain response to physiological and environmental cues.…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, we could not analyze the impact of menstrual cycle or contraceptive medication as the sample size was not large enough for further stratified analyses. Nonetheless, it is known that peripheral insulin sensitivity changes throughout the cycle [ 58 ] and also eating behavior and preferences may change [ 18 ] and should therefore be addressed in further experiments. Furthermore, peripheral insulin sensitivity was not assessed through hyperinsulinemic-euglycemic clamp but estimated with the widely-used Matsuda index from repeated insulin and glucose measurements during an oGTT [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study recruited young, healthy, regularly menstruating women and as such findings must be extrapolated to a broader population with caution. Elevated adiposity and insulin resistance are associated with greater perturbations in ovarian hormone concentrations and metabolic control across the menstrual cycle (5,6,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclical fluctuations in hormonal profiles between menstrual cycle phases are associated with variable metabolic control in regularly menstruating women. Studies report elevated glucose and insulin during the luteal phase, alongside reduced triglyceride and cholesterol (5)(6)(7)(8). Correspondingly, glycemic control, lipid control, insulin resistance and energy expenditure differ between menstrual cycle phases (6,7,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that adipose factors mainly from adipose tissue were associated with a variety of metabolic-related diseases, abdominal fat mainly produced harmful adipokines that led to worse clinical outcomes, while hip fat was the opposite (35-37). In addition, excessive abdominal fat can directly or indirectly cause sympathetic hyperactivity and abnormal secretion of adipose factors including adiponectin and leptin, which in turn leads to the occurrence and development of dyslipidemia, prethrombotic state (such as platelet activation), insulin resistance and chronic inflammation, which are the several established independent risk factors of CVD (19,(38)(39)(40). Therefore, the higher the WHR, the higher the risk of CVD, which may be mediated by abnormal fat distribution and adipokine dysfunction.…”
Section: Discussionmentioning
confidence: 99%